2023
DOI: 10.3390/genes14051048
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analyses of Leg Muscle during Early Growth between Geese (Anser cygnoides) Breeds Differing in Body Size Characteristics

Abstract: Goose is an important poultry commonly raised for meat. The early growth performance of geese significantly influences their market weight and slaughter weight, affecting the poultry industry’s economic benefits. To identify the growth surge between the Shitou goose and the Wuzong goose, we collected the early growth body traits from 0 to 12 weeks. In addition, we investigated the transcriptomic changes in leg muscles at the high growth speed period to reveal the difference between the two geese breeds. We als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…In this study, the expression of the MYLK2 gene was significantly higher at 4 and 8 wk of age than at 2 wk of age, the expression of the MYLK3 gene decreased gradually with the increase of weekly age, and the opposite was true for the MYLK4 gene, which is involved in the signaling pathways such as adhesion plaque, calcium signaling pathway, and the regulation of actin cytoskeleton, which may be related to the muscle growth and intercellular signaling, and play a key role. In a comparative transcriptomic study of the leg muscles of Shitou goose and Wuzong goose, it was similarly found that MYLK4 may be associated with growth and development ( Tang et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the expression of the MYLK2 gene was significantly higher at 4 and 8 wk of age than at 2 wk of age, the expression of the MYLK3 gene decreased gradually with the increase of weekly age, and the opposite was true for the MYLK4 gene, which is involved in the signaling pathways such as adhesion plaque, calcium signaling pathway, and the regulation of actin cytoskeleton, which may be related to the muscle growth and intercellular signaling, and play a key role. In a comparative transcriptomic study of the leg muscles of Shitou goose and Wuzong goose, it was similarly found that MYLK4 may be associated with growth and development ( Tang et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Focal adhesion pathway is significantly enriched in genes such as MYLK4, COL4A5, PARVA, etc., of which COL4A5 is thought to be possibly related to the transmission of cellular signals and substances, and the development and function of the blood system. A sound blood system can provide many nutrients for the growth of body tissues and promote the organism's growth ( Tang et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang identified seven growth-related genes through the comparative transcriptome analysis of Muscovy duck ileum tissue, providing a theoretical foundation for investigating the impact of the ileum on duck growth and metabolism [11]. Tang identified 290 and 87 differentially expressed genes associated with growth traits in the comparative transcriptome analysis of pituitary and muscle tissues from large and small geese, respectively [12,13]. Wen performed a comparative transcriptome analysis on muscle tissue from Tibetan sheep at four different growth stages, revealing that the LIPE, LEP, ADIPOQ, SCD, and FASN genes may modulate muscle fiber type transformation through the AMPK signaling pathway, consequently impacting meat quality [14].…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, Chinese goose meat production reached an impressive 570 million birds, accounting for 99% of Asia’s total and 94% of the global output. Furthermore, China achieved a goose meat yield of 1.77 million tons [ 2 ]. Renowned for its exceptional meat quality, the Sichuan white goose (Anser cygnoides domesticus) stands as a distinct local breed in China.…”
Section: Introductionmentioning
confidence: 99%